2006
DOI: 10.1128/jcm.02566-05
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Campylobacter fetus Subspecies by Phenotypic Differentiation and PCR

Abstract: The species Campylobacter fetus is divided into the subspecies C. fetus subsp. venerealis and C. fetus subsp. fetus, which differ in their epidemiologies and clinical importance. The differences between these subspecies make accurate distinction between the two essential. First, the value of seven key tests for the traditional differentiation of C. fetus was investigated. Afterwards, the results of the phenotypic differentiation and PCR were compared to address the question of the reliability of this PCR assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 13 publications
0
59
0
1
Order By: Relevance
“…Nevertheless, because of inappropriate standardization of biochemical tests, accurate identification of Campylobacter strains at the species level should include molecular methods. This is particularly true for C. fetus, which furthermore is divided into two different subspecies that have dramatic differences in their epidemiological and clinical implications (20). To the best of our knowledge, this is the first reported case of recurrent pleurisy caused by accurately identified C. fetus subsp.…”
mentioning
confidence: 86%
“…Nevertheless, because of inappropriate standardization of biochemical tests, accurate identification of Campylobacter strains at the species level should include molecular methods. This is particularly true for C. fetus, which furthermore is divided into two different subspecies that have dramatic differences in their epidemiological and clinical implications (20). To the best of our knowledge, this is the first reported case of recurrent pleurisy caused by accurately identified C. fetus subsp.…”
mentioning
confidence: 86%
“…Existence of atypical and mutant strains highlights that biochemical testing is not a reliable method for the differentiation of C. fetus subspecies and emphasises the need to perform more than one biochemical test to limit misidentification (Chang and Ogg, 1971;Hum et al, 1997;On, 1996;On and Harrington, 2001;On and Holmes, 1991a;Salama et al, 1992;Schulze et al, 2006;Vargas et al, 2003;Wagenaar et al, 2001 (Hazeleger et al, 1992;Hodinka and Gilligan, 1988;Nachamkin and Barbagallo, 1990). Of the three techniques, Microscreen appeared to be superior because of its ability to recognise a larger number of species, the absence of cross-reactions with non-Campylobacter spp.…”
Section: Biochemical Testingmentioning
confidence: 99%
“…A recent study obtained 100% correlation between PCR and biochemical phenotyping of 103 C. fetus isolates by using optimal inoculum size and two subsequent PCR assays instead of a multiplex PCR . Some studies reported that C. fetusspecific primers (MG3F and MG4R, Table 2) produced a fragment of 750 bp although others obtained a 960 bp amplicon (Hum et al, 1997;On and Harrington, 2001;Schulze, et al 2006;Vargas et al, 2003;Wagenaar, et al 2001, Willoughby, et al 2005. Sequencing determined the accurate C. fetus product size as 764 bp, targeting a carbon starvation protein (Hum et al, 2010).…”
Section: Venerealismentioning
confidence: 99%
See 2 more Smart Citations